Performance of IBS precast concrete beam - column connections under earthquake effects - Azlan Adnan, author; Tiong, Patrick Liq Yee, 1984-, author; Abdul Karim Mirasa, 1953-, author; Ahmad Baharuddin Abd. Rahman, author; Asia Pacific Structural Engineering and Construction Conference (7th: 2009: Langkawi) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL